Latvian pharmaceutical market: a review of marketing components and development trends - Kite, Matiss; Batraga, Anda; Salkovska, Jelena (University of Latvia, 2021)
In-depth market assessment is crucial prior making investments into product development and decisions on marketing strategy, especially in markets with small volume and low value like Latvian pharmaceutical market. Transparent market data and constant market reviews are expected to retain already existing pharmaceutical suppliers and attract new ones; although annual reports of general market figures are available publicly, reviews of pharmaceutical market marketing figures and activities are not being published. By assessing and studying Latvian pharmaceutical market and its marketing components the possible risks and development trends can be outlined and further addressed by pharmaceutical producers and suppliers. Purpose of the article: The purpose of the research is to assess Latvian pharmaceutical market figures, trends of its marketing key components and their influence on pharmaceutical entrepreneur marketing activities. The findings of this article could later be used by pharmaceutical entrepreneurs to align their marketing strategies for Latvian market and by governmental institutions to better understand pharmaceutical market composition and how the market could be governed to make it more attractive to pharmaceutical entrepreneurs. Objective: To review Latvian pharmaceutical market, its figures and trends of marketing components and outline market specifics for the use of potential entrepreneurs. Methodology/methods: In order to attain the goal and objectives, the following quantitative and qualitative methods were used: secondary data research of governmental reports and industry databases, content analysis of the recent scientific and professional literature available and in-depth interviews of pharmaceutical industry experts. The study is based on scientific papers published by foreign scholars, non-governmental organizations and reports from international organizations, governmental and industry bodies. Findings: Latvian Pharmaceutical market is quite dependent on supplies from foreign producers, but due to low pharmaceutical product prices and small market volume, there is a risk for product supply disruptions and shortages. Over the counter pharmaceutical product demand and promotion activities are linked to seasonal trends; for prescription products relationships with key opinion leaders and other public relations are the main focus of marketing activities.
Keywords: Pharmaceutical Market; Pharmaceutical Pricing; Pharmaceutical distribution; Marketing; Research Subject Categories::SOCIAL SCIENCES::Business and economics